MEMBANGUN KEPEMIMPINAN KOLABORATIF UNTUK MASYARAKAT BERKELANJUTAN - Richnalendra, Alvyanito; Ridha, Ahmad Husnan; Rahman, Rusyda Nasyita; Agustinova, Danang Ade (STKIP Pesisir Selatan, 2025)
Global transformation has changed the leadership paradigm, from a hierarchical approach to a more inclusive and adaptive collaborative model. This research aims to explore the concepts, principles, and implementation of collaborative leadership in supporting sustainable development, highlighting the challenges and opportunities in Indonesia. The research method uses a literature study approach that analyzes various academic sources and related case studies. The results show that collaborative leadership, which focuses on cross-sector synergy, is able to increase the effectiveness of solutions to multidimensional challenges. The case study of the Gandeng Gendong Program in Yogyakarta shows the success of this approach in improving community welfare, although it still faces obstacles such as lack of socialization and coordination. In conclusion, collaborative leadership is an important strategy for creating inclusive and sustainable communities, with recommendations on improving communication,trust and conflict management as priorities.